Financial Sector Development and Economic Growth: Evidence from Zimbabwe - Ndlovu, Godfrey (International Journal of Economics and Financial Issues, 2013)
The relationship between financial system development and economic development has attracted interest of a number of researchers all over the world, however institutional differences and capital allocation variations between and within economies, make it very difficult to generalize findings and thus increasing the need for country-specific studies. This study examines the causal relation between financial system development and economic growth from a Zimbabwean perspective, based on two inter-related broad aims, the first being the established of cointegration relationship between the two and the ultimate direction of the causal relationship. Using multivariate Granger causality test the study finds existence of demand following financial development in Zimbabwe, there is unidirectional causality from economic growth to financial development. Financial system development is therefore an outcome of the pressure for institutional development in capital markets and introduction of modernized financial instruments. As such policy concern should focus on trade liberalization and other related activities in order to spur economic growth, since financial system development is a passive reaction to economic growth. Such policies might include investment promotion and removal of barriers for foreign investments. Keywords: Financial system development; economic growth; poverty alleviation; granger causality JEL Classifications: C22; E44; G10; O11; O40